USIA NIKAH PERSPEKTIF MAQASHID PERKAWINAN: TELAAH SYARAT USIA MINIMUM PERKAWINAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR:22/PUU-XV/2017 - Moch Nurcholis (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2020)
This research departs on academic anxiety related to the rationale of determining marriage age requirements in the statute, which is not regulated in classical fiqh. The main issues to be examined are concerning: (1) Determination of marriage age requirements according to Islamic law (2) Equalization of male and female marriage ages according to Islamic law (3) Correlation of equal marriage age with marriage maqashid. The results of the study concluded that; (1) Determination of the age requirement of marriage, however it is not discussed in classical fiqh, but has an academic foundation in accordance with Islamic law; (2) Equalization of male and female marriage age is in accordance with the principle of equality (al-musawah) in Islamic law; (3) Equalization of marriage age has a positive correlation in realizing maqashid marriage.